A Flexible Rechargeable Zinc–Air Battery with Excellent Low‐Temperature Adaptability. Issue 12 (4th February 2020) - Pei, Zengxia; Yuan, Ziwen; Wang, Chaojun; Zhao, Shenlong; Fei, Jingyuan; Wei, Li; Chen, Junsheng; Wang, Cheng; Qi, Rongjie; Liu, Zongwen; Chen, Yuan
Abstract: Flexible zinc–air batteries (ZAB) are a promising battery candidate for emerging flexible electronic devices, but the catalysis‐based working principle and unique semi‐opened structure pose a severe challenge to their overall performance at cold temperature. Herein, we report the first flexible rechargeable ZAB with excellent low‐temperature adaptability, based on the innovation of an efficient electrocatalyst to offset the electrochemical performance shrinkage caused by decreased temperature and a highly conductive hydrogel with a polarized terminal group to render the anti‐freezing property. The fabricated ZABs show excellent electrochemical performances that outperform those of many aqueous ZABs at room temperature. They also deliver a high capacity of 691 mAh g −1 and an energy density of 798 Wh kg −1 at −20 °C (92.7 % and 87.2 % retention of the room temperature counterparts, respectively), together with excellent flexibility and reverting capability. Abstract : Powering the frozen world : The first flexible zinc–air battery with excellent low‐temperature adaptability was achieved through the development of an innovative air‐cathodic electrocatalyst and hydrogel electrolyte. The battery delivers a capacity of 691 mAh g −1 and an energy density of 798 Wh kg −1 at −20 °C, along with excellent flexibility and state‐of‐the‐art low‐temperature performance.